IMPACT OF THE DEPTH OF WINTER WHEAT SEED WRAPPING ON ITS STRUCTURAL ELEMENTS AND YIELD - Lykhochvor , В.; Petrychenko , В.; Andrushko , О.; Kosylovych , Г.; Olifir , Ю. (Bulletin of Lviv National Environmental University. Series Agronomy, 2023)
To establish the optimal depth of winter wheat seed wrapping in conditions of the Western Forest Steppe in 2018–2020, field studies were conducted on the dark-gray podsolized light loam soil of the experimental field of the Department of Technologies in Crop Production of Lviv National Environmental University. On September 30, the RZhT Reform variety was sown with a seeding rate of 3.0 million/ha and row spacing of 15 cm. The mineral fertilizer application rate was N180Р46K60. The studied depthes of seed wrapping were 1 cm, 2 cm, 3 cm, 4 cm, 5 cm, 6 cm and 7 cm. It was established that the length of the root-like internode (distance from the primary root system to the node of the tiller) increased when the depth of seed wrapping increased and was the largest in the variant of sowing at the depth of 7 cm – 4.5 cm. The depth of seed wrapping did not affect the crop overwintering. The highest rates of field germination (90 %) of winter wheat were obtained when sowing at the depth of 2 cm and 3 cm. The same depth of seed wrapping provided proper conditions for intensification of the tillering process. The coefficient of tillering increased up to 2.4 and 2.5. The density of productive stem of winter wheat was also the highest at the sowing depth at 2 cm and 3 cm, i.e. 634 units/m2 and 652 units/m2 respectively. The mass of grain from an ear was lower (1.32–1.34 g) when sowing at a depth of 2–4 cm, which was caused by better conditions for creating higher density of ears in these variants. In the variants with a higher or lower sowing depth, the conditions for tillering were complicated, and the yield depended more on the weight of grain from the ear. To get the highest yield, the optimal combination of the main elements of the structure of productive stem density and the weight of the grain from the ear is: 634 ears × 1.34 g and 652 ears × 1.32 g per m2. The best conditions for implementation of the genetic potential of winter wheat productivity of the RZhT Reform variety and obtaining the yield of 8.22 t/ha and 8.30 t/ha are created at the sowing depth of 2 cm and 3 cm. The yield is smaller in the variants of shallow and deep seed wrapping. In the version of sowing at the depth of 7 cm, it was the smallest and amounted to 7.30 t/ha.